Heating, ventilating, and air conditioning : analysis and design - McQuiston, Faye C. 1928- (John Wiley and Sons, 1994)
Introduction. Air-conditioning systems. Moist air properties and conditioning processes. Indoor air quality-comfort and health. Heat transmission in building structures. Solar radiation. Space heat load. The cooling load. The cooling load. Energy calculations. Flow, pumps, and piping design...